The study of movement wide span tractor (vehicles) with kinematic (turn of wheels) method of its control - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Kiurchev, Volodymyr; Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Nadykto, Volodymyr; Надикто, Володимир Трохимович; Надыкто, Владимир Трофимович; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; et al. (My University, 2017)
Prospective energy technology devises for controlled traffic farming is the wide span tractor (vehicles). Their driving can be built behind the kinematic or force principle of the turn. At the kinematic turn, the schemes are applied by turning the steered wheels (front, rear or both front and rear) relative to the car's frame. The widest distribution in wide span tractor (vehicles) was obtained by turning schemes with all steerable wheels. The theoretical foundations of the dynamics of the parallel-span parallel motion tractor (vehicles) in the horizontal plane are presented in the article under the kinematic method of its control (by turning the wheels). Theoretical research is based on the basic principles of theoretical mechanics, tractor theory, statistical dynamics and the theory of automatic control of linear dynamical systems when they reproduce statistically random control and disturbing input effects. The amplitude and phase frequency characteristics are based on the analysis of the evaluation of the degree of influence of the circuit and parameters of the investigated wide span tractor (vehicles) on its controllability and stability of motion. The physical object of the theoretical studies was the prototype of the wide span tractor (vehicles) of the new design. Mathematical models of the wide span tractor (vehicles) movement are represented in the differential and operator form of recording. On the basis of mathematical models, the calculated amplitude and phase-frequency characteristics of the dynamic control system development are plotted, represented by the average rotation angle of the front wheels of the wide span tractor (vehicles). The constructed mathematical models, amplitude and phase-frequency characteristics allow estimating the effect of the control parameter of the wide span tractor (vehicles), as well as its design and other parameters on the controllability and stability of motion.
Keywords: controlled traffic farming; wide span tractor (vehicles); theoretical studies; kinematic method of control